FENOMENA PENJUALAN POP NFT (Arthavidya Jurnal Ilmiah Ekonomi, 2023)
At the beginning of 2022, the public was in an uproar because Ghozali, a student, suddenly became a billionaire just by selling selfies in NFT form on OpenSea. The name of his NFT is Ghozali Everyday. Not only had it become a topic of discussion in Indonesia, the Ghozali Everyday had also become the subject of news in Singapore, India, Philippines, England, and even United State of America. This study aims to analyze why and how the Ghozali Everyday could occur. By analyzing 280 samples of Ghozali Everyday NFT, this study found that what happened to Ghozali Everyday was a pop sales phenomenon. And, using the netnographic method, this study found that Ghozali Everyday's pop sales occurred due to several factors, i.e. community, momentum, low prices, and promotions. To the best of the author's knowledge, this is the first research on Ghozali Everyday. Thus, this study will add a new literature in NFT research that are still scarce